Engaging characters : fiction, emotion, and the cinema - Smith, Murray (Murray Stuart) (Oxford : Clarendon Press ; New York : Oxford University Press, 1995)
1. The Saliency of Character##2. The Imaginative Spectator##3. Engaging Characters##4. The Threshold of Legibility: Recognition##5. Screens and Filters: Alignment##6. Soot and Whitewash: Allegiance.
Includes bibliographical references (p. [243]-254) and index.
boek